PI3K inhibition modulates PON gene expression and disrupts survival pathways in retinoblastoma Y-79 cells - Ramya Ravi; Sathik Shajahan; Jayavigneeswari Suresh babu; S. R. Bharathi devi (Molecular Biology Reports, 2026)

Interplay between NOD1 polymorphisms and gene expression in the pathogenesis of gallstone disease - Sanjana Murali; Shanthi Vijayaraghavan; Rajesh Kumar Shanmugam; Nandini Krishnamurthy; R B Devi Krishna; Pradeep Narahari Ram; Jashwanth Balu; Andrea Mary Francis (Molecular Biology Reports, 2026)

Partial substitution of herbicides with sorghum allelopathic extract and its impact on productivity of wheat and soil microbes - Devi Lal Kikraliya; U. N. Shukla; Krishna Saharan; A. K. Meena; Moola Ram; R. C. Meena (Brazilian Journal of Microbiology, 2026)

Studies on the immunological biomarkers of bovine tuberculosis in naturally infected cattle - Shalini Sharma; Gursimran Filia; Geeta Devi Leishangthem; R S Sethi; Gurpreet Kaur (Brazilian Journal of Microbiology, 2026)

Integrated GC–MS/MS and LC–MS/MS determination of potential genotoxic impurities in HER2 inhibitor tucatinib with in silico toxicological risk assessment and green analytical evaluation - Venkateswara Rao Bhoomi; Tentu Nageswara Rao; T.B. Patrudu; R. Uma Devi; Anil Kumar Kanuri (Next Research, 2026)

Submergence Tolerance in Rice: Genetic Mechanisms, Physiological Adaptations, and Breeding Strategies of Flood Resilience - S. Manju Devi; S. Vignesh; A. John Joel; M. Raveendran; R. Pushpa; R. Suresh (Plant Molecular Biology Reporter, 2026)

Trade-offs and Synergies of Soil Restoration Through Conservation Tillage: Strategies for Sustainable Agri-Food Systems in Riverine Agroecosystems - S. Pazhanisamy; Rodda Chandana Devi; Sunita Kumari Meena; E. Rathinaguru; R. Sushma Devi; S. Mala; Dinesh Jinger; Raj Kumar Jat; H. S. Jat; Vijay Singh Meena; M. L. Jat (Anthropocene Science, 2026)

Bioactive compounds of Glycyrrhiza glabra and their functional role in modulating gut inflammation and intestinal homeostasis - Devi Basumatary; Abhipsha Saikia; Mohit Pandey; Jagat C. Borah; Mojibur R. Khan (Inflammopharmacology, 2026)

Planthopper-induced vulnerability: amplifying fall armyworm, Spodoptera frugiperda (J.E. Smith) preference in rice - V. Chinna Babu Naik; S. Rakhesh; D. Devi Pratyusha; K. A. V. Sindhura; Kokkula Akhilesh; K. Vani Sree; R. M. Sundaram (Phytoparasitica, 2026)

Application of bioencapsulated microalgae in marine cladoceran (Penilia sp.) for enhancing growth and improve production of Asian seabass (Lates calcarifer) - K. Nanthini Devi; P. Santhanam; A. Shenbaga Devi; P. Raju; R. Sagaya Princy; K. Rajagopal; I. S. Bright Singh; A. S. Sahul Hameed; A. Jishnu Panamoly; P. Perumal (Journal of Applied Phycology, 2026)

Unveiling the prevalence, pathogenic and molecular characterization of Xanthomonas strains responsible for bacterial leaf spot of tomato and pepper in India - P. Lokesh Babu; V. Devappa; J. Rajender; Neelam Geat; R. S. Devi; Rahul Patidar; Ainmisha Singh; V. K. Banarwal; Jasdeep Chatrath Padaria; Anju Kamra; Dinesh Singh (Journal of Plant Pathology, 2026)

Probiotic Lactiplantibacillus plantarum strains attenuate Salmonella-induced inflammation through coordinated cytokine and redox regulation - Parijat Hazarika; Deepjyoti Kalita; Parag Medhi; Chingtham Thanil Singh; Devi Basumatary; Mojibur R. Khan (World Journal of Microbiology and Biotechnology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Hierarchical SPEES nanocomposite ionomer with phosphomolybdic acid decorated Co3O4 nanofiller as PEM for microbial fuel cells: An anti-biofouling and scale-up approach - John Solomon; Akshaya Senthilkumar; Naveen Rajkumar Sivakumar; R. Devi; Sangeetha Dharmalingam (Journal of Environmental Management, 2026)

Utilization of crop wild relatives in genetic improvement of bitter gourd, Momordica charantia L. - S. Devi; R. Neelavathi; C. Indu Rani; R. Kalaiyarasi; K. Gurusamy (Genetic Resources and Crop Evolution, 2026)

Beneficial effects of Musa balbisiana fruit pulp and Garcinia candy on gut microbiota alterations of aged albino Wistar rats - Partha Pratim Sarma; Santanu Das; Swarnali Bhattacharjee; Mojibur R. Khan; Rajlakshmi Devi (PharmaNutrition, 2026)

RSM-ANN-GA framework for predictive modeling and optimization of sonocatalytic eosin dye degradation using ZnO@SiO2 nanocomposites - G.V. Aatral; V. Chitra Devi; S. Mothil; R. Sathish Raam (Journal of Contaminant Hydrology, 2026)

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Subsurface drip fertigation optimizes nitrogen distribution in soil under maize cultivation - Arjun Singh; Anchal Dass; Susama Sudhishri; V. K. Singh; R. N. Sahoo; Kapila Shekhawat; Pravin K. Upadhyay; S. S. Rathore; Ayekpam Dollina Devi (Plant and Soil, 2026)

Unravelling Ovarian Cancer: an analysis of the Influence of LRP1 and PAI1 Genetic Variations - R. B. Devi Krishna; Sneha Grace Mathews; Preet Agarwal; C. Elizabeth Rani; Nandini Krishnamurthy; Sanjana Murali; A. Lohitha Rani; Leena Dennis Joseph; Banukeerthana Rajasekaran; F. Andrea Mary (Biochemical Genetics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Integrated Nutrient Management: An Effective Strategy to Mitigate Greenhouse Gas Emission and Global Warming Potential Under Rice Cultivation - Naorem Twinkle Devi; Angom Sarjubala Devi; R. S. Khoiyangbam (Agricultural Research, 2026)

Enhanced tannery wastewater remediation using a synergistic Bacillus licheniformis and Auxenochlorella pyrenoidosa consortium - Anuradha Devi; Devendra Kumar Patel; Gubbala Naga Venkata Satyanarayana; Vartika Jain; Ganesh Dattatraya Saratale; Luiz Fernando R. Ferreira; Ram Naresh Bharagava (Environmental Sustainability, 2026)

Conservation agriculture for riverine agri-food systems under the climate crisis: enhancing soil health and mitigating erosion - Pazhanisamy S.; Devendra Singh; Rodda Chandana Devi; Vijay Singh Meena; Sunil Kumar; R.S. Singh; S.S. Prasad; R. Sushma Devi; Jogdande Sai Prasad; K. Damodar; Abhinandan Singh; V. Sridevi; et al. (Soil and Tillage Research, 2026)

Ingenious design and application of ZnAl-LDH/BiOBr Z-scheme heterojunction for effective photocatalytic degradation of tetracycline in aqueous environment: Insight into mechanism and toxicity estimation - R. Janani; M. Kanagalakshmi; S. Gopika Devi; Anitha Pius (Process Safety and Environmental Protection, 2026)

Edible synbiotic film based on soy protein reinforced with nanocellulose synthesized from jackfruit residues and probiotic (Lactobacillus pentosus) for feta cheese packaging - B. Pooja; R. Preetha; V. Sreejit; S. Maanila Devi (Food Bioscience, 2026)

Exploring the microbial basis of postbiotic and paraprobiotic therapy in ulcerative colitis - N. Pavithra; M. Devi; S. Nirenjen; B. Keerthana; V. K. Giresh kumar; R. Yogalakshmi; M. G. Priyadharshni; N. Harikrishnan (Archives of Microbiology, 2026)

Energetics of intense substorms of solar cycle 23 - Devi R. Nair; P. R. Prince (Acta Geophysica, 2025)

Comparative Flood Risk Mapping Using Knowledge-Driven, Data-Driven, and Ensemble Models in a Humid Tropical River Basin in India - Chandini Padmanabha Panicker Chandr Senan; Rajendran Shobha Ajin; B. R. Anaswara Devi; A. Rajaneesh; Jitendra K. Nagar; K. S. Sajinkumar (Water Conservation Science and Engineering, 2025)

Unlocking the Potential of Arbuscular Mycorrhizal Fungi: Exploring Role in Plant Growth Promotion, Nutrient Uptake Mechanisms, Biotic Stress Alleviation, and Sustaining Agricultural Production Systems - Ingudam Bhupenchandra; Sunil Kumar Chongtham; Ayam Gangarani Devi; Pranab Dutta; Manas Ranjan Sahoo; Sansuta Mohanty; Sumit Kumar; Anil K. Choudhary; Elangbam Lamalakshmi Devi; Soibam Sinyorita; Soibam Helena Devi; M. Mahanta; et al. (Journal of Plant Growth Regulation, 2025)

Correction: Extended distribution, key field notes, and morphological variations in endemic Garcinia dhanikhariensis S.K. Srivastava: a step towards domestication - Pooja Bohra; Ajit Arun Waman; R. Karthika Devi (Genetic Resources and Crop Evolution, 2025)

Extended distribution, key field notes, and morphological variations in endemic Garcinia dhanikhariensis S.K. Srivastava: a step towards domestication - Pooja Bohra; Ajit Arun Waman; R. Karthika Devi (Genetic Resources and Crop Evolution, 2025)

Real-time earthquake magnitude estimation utilizing a mixed dataset set of observed and simulated P-wave onsets for the Kumaon Himalaya from Mw3.0–7.5 earthquakes - Suraj Kumar Pal; S. Devi; Sandeep; P. Kumar; A. Joshi; Monika; R. Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Ecological features of zooplankton (copepods) in the perennial oceanic oxygen minimum zone in the Eastern Arabian Sea - V. Vidhya; R. Jyothibabu; K.T. Alok; N. Arunpandi; C.P. Rashid; R. Thirumurugan; C.R. Asha devi; G.V.M. Gupta (Marine Environmental Research, 2025)

Transforming waste management: leveraging recycletransformernet for effective recycling strategies - A. Devi; Amirtha Saravanan; R. Reeta; V. P. Anitha (Clean Technologies and Environmental Policy, 2025)

Investigation of the Optical and Photoluminescence Properties of CaF2: Dy3+ Nanoparticles Synthesized Via Solution Combustion Method for Optoelectronic Applications - N. Sushilal Devi; M. R. Shiekh; L. Raghumani Singh; A. Nabachandra Singh (Journal of Fluorescence, 2025)

Utilization of genetic diversity and marker trait association to improve anaerobic germination tolerance in rice (Oryza sativa L.)‏ - S. Manju Devi; A. John Joel; M. Raveendran; R. Pushpam; S. Muthuramu; R. Pushpa; N. Sritharan; R. Suresh (Genetic Resources and Crop Evolution, 2025)

Microbial diversity, enzyme activity, metal contamination, and their responses to environmental drivers in an Indo-Burmese freshwater wetland - Anasuya Bharadwaj; Santanu Das; Mojibur R. Khan; Arundhuti Devi (Environmental Research, 2025)

Production and Extraction of Red Bioactive Pigment from Streptomyces griseorubiginosus and Formulation of Bio-Lip Balm - S. Vignesh; P. M. Anandu; G. S. Gopuraj Varrier; Nikhil Brijmohan; G. Gokula Krishnan; Sanjeev K. Ganesh; Sreelakshmi R. Nair; V. Mohanasrinivasan; C. Subathra Devi (Indian Journal of Microbiology, 2025)

Insecticidal Potential of Essential Oil and Sesquiterpene Alcohols from Leaves of Clausena indica (Dalz.) Oliver Against Spodoptera litura, Helicoverpa armigera, and Tribolium castaneum Under Laboratory and Field Conditions - J. Achyutha Devi; R. Thangapandian; C. Vijayaraghavan; Raja Rama Devi Patel; S. Ravi Kiran (Neotropical Entomology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Unveiling the interaction, cytotoxicity and antibacterial potential of pyridine derivatives: an experimental and theoretical approach with bovine serum albumin - Rosalin Das; Patitapaban Mohanty; Pragyan P. Dash; Swagatika Mishra; Ajit K. Bishoyi; Lokanath Mishra; Laxmipriya Prusty; Devi P. Behera; Debasmita Dubey; Monalisa Mishra; Harekrushna Sahoo; Mohd S. Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Spatial preferences influence associations between magnitude and space in honey bees - Jung-Chun (Zaza) Kuo; Leslie Ng; Devi Stuart-Fox; Adrian G. Dyer; Scarlett R. Howard (Animal Behaviour, 2025)

Nanoplastics in heat-sensitive food packaging: A review of migration, detection, health, and environmental impacts - Senthilkumar Palanisamy; Barani Kumar Saravana Kumar; Aishwarya Vetrivel; Rahul Jacob Michael; Nivethitha Babu; Sanjay Sharan Nallamuthu; Kokila Saravanan; Shanmugam Venkatachalam; Naveen Kumar R J; Gayathri Devi Selvaraju; Rajendran K. Selvakesavan; Jintae Lee; et al. (Food Control, 2025)

Eco-phenological drivers of black gram (Vigna mungo (L) Hepper) productivity in diverse environments and their implications for crop improvement - Ashok K. Parihar; Kali Krishna Hazra; Amrit Lamichaney; Debjyoti Sen Gupta; Anil K. Singh; Jai Dev; Samuel Jaberson; Ajaj A. Lone; S.P. Das; Shayla Bindra; R.K. Panwar; Ashok Kumar; et al. (Field Crops Research, 2025)

Photodegradation of methylene blue from waste water under visible light and bacterial growth inhibition by GO and rGO blended CdO: Mn nanoparticles– a comparative study - N. Manjula; A. R. Balu; B. Sowmiya Devi; S. Chitra Devi; K. Devendran; M. Sriramraj; S. Adityan; A. Vinith (Nanotechnology for Environmental Engineering, 2025)

First report of leaf spot disease on Zanthoxylum rhetsa caused by Fusarium solani-melongenae in India - N. Surmina Devi; T. Shantibala; Arunkumar Phurailatpam; N. Y. Chanu; Anju Choudhury; Priyanka Irungbam; P. Raja; R. C. Shakywar (Indian Phytopathology, 2025)

Variations in horticultural characteristics in Garcinia gummi-gutta (L.) N. Robson: a cash crop of the humid tropics of India - Pooja Bohra; Ajit Arun Waman; R. Karthika Devi (Genetic Resources and Crop Evolution, 2025)

Ecophysiological status of copepods in the oxygen minimum zone of Eastern Arabian Sea - V. Vidhya; R. Jyothibabu; K.T. Alok; C.P. Rashid; N. Arunpandi; C.R. Asha Devi; G.V.M. Gupta; R. Thirumurugan (Marine Pollution Bulletin, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Mimicking characteristics of cast iron for enhanced electrocatalytic dehydrogenation of methane - Tushar Singh Verma; R. Nandini Devi; Sailaja Krishnamurty (Fuel, 2025)

Large scale screening and quantification of micropollutants in fish from the coastal waters of Cochin, India: Analytical method development and health risk assessment - Nasreen Nazar; A.S. Athira; R. Devi Krishna; Satyen Kumar Panda; Kaushik Banerjee; Niladri Sekhar Chatterjee (Science of The Total Environment, 2024)

Garcinol enriched fraction of Garcinia morella (Gaertn.) Desr. fruit rind improves gut health and reduces the risk of nonalcoholic fatty liver disease by regulating PCK1/ACC/SREBP1/FASn pathway in a mouse model - Devi Basumatary; Santanu Das; M. Bidyarani Devi; G. Shalini Devi; Pranamika Sarma; Ashis K. Mukherjee; Mojibur R. Khan; Jagat C. Borah (Food Research International, 2024)

Dissecting genetic variation for agro-morphological traits of elevated temperature under CO2-temperature gradient chamber and validation of markers linked to heat tolerance of rice (Oryza sativa L.)‏ cultivars of north-eastern Himalayan Region - Amit Kumar; Letngam Touthang; Shankar. P. Das; R. Krishnappa; Avinash Pandey; Arvind Prasad; Shiv Poojan Singh; Simardeep Kaur; C. Aochen; Veerendra Kumar Verma; N. Umakanta; A. Gangarani Devi; et al. (Euphytica, 2024)

First report of Wangiella dicollaria Nie, 1934 from the Eastern Arabian Sea with notes on the status of Stenosemella parvicollis (Marshall, 1934) Hada, 1935 - I. Anandavelu; C. R. Asha Devi; Sambit Singh; Mintu Chowdhury (Marine Biology Research, 2024)

Multifunctional electrospun membranes incorporated with metal oxide nanoparticles, cellulose acetate, and polyvinylpyrrolidone for wastewater treatment: Oil/water separation, dye adsorption, and dye degradation - Chaithra K P; Arun Varghese; Vinod T. P.; Sunaja Devi K. R. (Chemical Engineering Journal, 2024)

A multi-faceted approach involving laboratory assay, glasshouse, and field experiments in identifying stem rot (incited by Sclerotium rolfsii Sacc.) resistance in advanced breeding lines of groundnut - Manasa Ramaraju; R. Sarada Jayalakshmi Devi; K. Vemana; K. John; G. Rama Rao; Hari Kishan Sudini (Australasian Plant Pathology, 2024)

Exploring Holy Basil’s Bioactive Compounds for T2DM Treatment: Docking and Molecular Dynamics Simulations with Human Omentin-1 - Mohammad Jasim Ibrahim; Aayushi Nangia; Soumik Das; Tanishque Verma; V. Devi Rajeswari; Ganesh Venkatraman; R. Gnanasambandan (Cell Biochemistry and Biophysics, 2024)

Real-time urban flood modeling: exploring the sub-grid approach for accurate simulation and hazard analysis - R. Reshma; N. Nithila Devi; Soumendra Nath Kuiry (Natural Hazards, 2024)

Synthesis, Structural, Spectroscopic, Fluorescence, and Dielectric Studies of Bis-(4-Aminopyridine)-Zinc(II) Acetate: A Metal–Organic Crystal - Helen Merina Albert; R. Priya; Bajirao Bhila Ahire; N. S. M. P. Latha Devi; J. Madhuri Sailaja; S. Raziya Tabassum; Nellore Manoj Kumar; C. Alosious Gonsago (Journal of Fluorescence, 2024)

Spatial analysis and assessment of soil erosion in the southern Western Ghats region in India - Anand B.; Remitha K.R.; Shanmathi Rekha R.; Midhuna Devi M.; Ramaswamy K. (Environmental Monitoring and Assessment, 2024)

Potato Yield Classification Using Weather Variables: a Discriminant Analysis Approach - S. R. Krishna Priya; N. Naranammal; Walid Emam; Yusra Tashkandy; Monika Devi; Pradeep Mishra (Potato Research, 2024)

Climatology of thermodynamic indices and background synoptic conditions responsible for severe convection during pre‐ to post‐monsoon seasons over Indian region - A. Madhulatha; M. Mohapatra; K. Sathi Devi; D. R. Pattanaik; M. Rajeevan; Anand Kumar Das; R. K. Jenamani; Naresh Kumar (International Journal of Climatology, 2024)
To investigate the mechanisms responsible for severe convection linked with a variety of mesoscale, synoptic systems over the Indian region, a preliminary analysis is conducted. Using IMD RSRW/Reanalysis (ERA5)/Lightning (TRMM LIS) products both local‐scale thermodynamics and large‐scale background conditions responsible for the major lightning hot spots in different seasons are investigated. In the pre‐monsoon season, high lightning activity over NE Indian region is due to moisture intrusion by south‐westerly at lower levels (warm air advection), along with mid‐level north westerlies (cold air advection) which favour the low‐level convergence and upper‐level divergence. SCS over south India are mainly attributed to wind discontinuity over the region. During monsoon season major lightning activity in NW India is due to the presence of heat low and the rest of the country less intense SCS activity is evident due to high wind shear conditions in connection with low‐level (westerly) and upper‐level (easterly jet stream). In the post‐monsoon season, major lightning in south India are due to the prevailing north‐easterlies and in north India, the activity is attributed to the passage of western disturbance (WD). Station plot analysis suggests the varied distribution of thermodynamic indices season/region‐wise due to the diverse background forcing. Correlation analysis between the lightning and thermodynamic indices suggests that more skillful indices are KI (~0.7 to 0.8), precipitable water (PPW) (~0.8) (pre‐monsoon, monsoon) and (PPW) (~0.8), convective available potential energy (CAPE) (~0.6) in post monsoon over respective lightning hot‐spot regions. Independent verification using Wyoming data/reanalysis for different case studies suggests that monitoring the monthly thresholds of highly correlated indices provides a helpful proxy to operationally forecast the severe convective systems (season/region). Mean Equivalent potential temperature, and mixing ratio in mixed layer has shown reasonable association with the lightning occurrence over all lightning hot spot regions which are implemented in the IMD GFS and IMD WRF models.

Research progress of MXenes and MXenes-based catalysts for photocatalytic water splitting: A systematic review - Sneha Ravi Kali; Meghana V; Madhushree R; Sunaja Devi K.R.; Dephan Pinheiro (Journal of Environmental Chemical Engineering, 2024)

Electric vehicles and health: A scoping review - Audrey F. Pennington; Cheryl R. Cornwell; Kanta Devi Sircar; Maria C. Mirabelli (Environmental Research, 2024)

Rice physical defenses and their role against insect herbivores - Devi Balakrishnan; Nick Bateman; Rupesh R. Kariyat (Planta, 2024)
Main conclusion Understanding surface defenses, a relatively unexplored area in rice can provide valuable insight into constitutive and induced defenses against herbivores. Abstract Plants have evolved a multi-layered defense system against the wide range of pests that constantly attack them. Physical defenses comprised of trichomes, wax, silica, callose, and lignin, and are considered as the first line of defense against herbivory that can directly affect herbivores by restricting or deterring them. Most studies on physical defenses against insect herbivores have been focused on dicots compared to monocots, although monocots include one of the most important crops, rice, which half of the global population is dependent on as their staple food. In rice, Silica is an important element stimulating plant growth, although Silica has also been found to impart resistance against herbivores. However, other physical defenses in rice including wax, trichomes, callose, and lignin are less explored. A detailed exploration of the morphological structures and functional consequences of physical defense structures in rice can assist in incorporating these resistance traits in plant breeding and genetic improvement programs, and thereby potentially reduce the use of chemicals in the field. This mini review addresses these points with a closer look at current literature and prospects on rice physical defenses.

Copepoda community imprints the continuity of the oceanic and shelf oxygen minimum zones along the west coast of India - V. Vidhya; R. Jyothibabu; N. Arunpandi; K.T. Alok; C.P. Rashid; R. Thirumurugan; C.R. Asha Devi; G.V.M. Gupta (Marine Environmental Research, 2024)

Mycorrhiza in Improving Morpho-Physiological and Biochemical Parameters of Chickpea Genotypes (Cicer arietinum L.) Under Salinity Stress - Pooja Pooja; Sridevi Tallapragada; Minakshi Yadav; R. K. Chugh; Sakshi Saini; Sarita Devi (Journal of Crop Health, 2024)

Factors regulating proliferation and co-occurrence of loricate ciliates in the microzooplankton community from the eastern Arabian Sea - C. R. Asha Devi; Jhimli Mondal; N. N. S. Vishnu; C. K. Sherin; K. J. Albin; I. Anandavelu; G. V. M. Gupta (Aquatic Sciences, 2024)

Microtubules assembly inhibitors in combination with PPO, ACCase and ALS inhibitors herbicides for the management of multiple herbicide-resistant Phalaris minor in wheat under Indo-Gangetic Plains: a threat to sustainable wheat production - Sushil Kumar; R. S. Dadarwal; Todar Mal; Akshit; Priyanka Devi; Pardeep Kumar; Bhupesh Dhaka (Acta Physiologiae Plantarum, 2024)

Whole genome sequencing of bacteriophage NINP13076 isolated against Salmonella enteritidis - R Naveen Kumar; Ashok Selvaraj; Tamilzhalagan Sembulingam; Virendra Panpatil; Kaliaperumal Venkatesh; S.D.G. Gowthami; Uday kumar Putchaa; Uma Devi Ranganathan; Hemalatha Rajkumar; Sudip Ghosh; Ramalingam Bethunaickan (Ecological Genetics and Genomics, 2024)

Single-cell classification, analysis, and its application using deep learning techniques - R. Premkumar; Arthi Srinivasan; K.G. Harini Devi; Deepika M; Gaayathry E; Pramod Jadhav; Abhishek Futane; Vigneswaran Narayanamurthy (BioSystems, 2024)

An investigation on the distribution dynamics of kiddi prawn, Parapenaeopsis stylifera (H. Milne Edwards, 1837) along southwest coast of India, using multi-dimensional approach - Dineshbabu A.P.; Maheswarudu G.; Josileen Jose; Lakshmi Pillai S.; Chakraborty Rekha Devi; Jinesh P.T.; Ragesh N.; Sreesanth L.; Shailaja Salian; Akash S.; Ratheeshkumar R.; Zacharia P.U.; et al. (Regional Studies in Marine Science, 2024)

Native bio-control agents from the rice fields of Telangana, India: characterization and unveiling the potential against stem rot and false smut diseases of rice - Sowmya Vanama; N. S. Raja Gopalan; Maruthi Pesari; M. Baskar; Uma Devi Gali; D. Ladha Lakshmi; P. Koteshwar; G. Jesudasu; Santosha Rathod; M. Srinivas Prasad; Rajanikanth Panuganti; R. M. Sundaram; et al. (World Journal of Microbiology and Biotechnology, 2024)

Centella asiatica Leaf Extract Mediated One-Pot Green Synthesized rGO Decorated PbS/CdO Nanocomposite for Catalytic Degradation of Methyl Violet from Wastewater and Resistance Against Bacillus subtilis and Pseudomonas aeruginosa Bacterial Strains - M. Suganya; A. R. Balu; S. Chitra Devi; K. Usharani; M. Sriramraj; K. Devendran; S. Adityan (Water, Air, & Soil Pollution, 2024)

Arctic–midlatitude–tropics interactions in January 2020: linkages to precipitation extremes over Indian region - S. D. Sanap; M. Mohapatra; D. R. Pattanaik; S. Sunitha Devi; Satendra Kumar; A. Kashyapi (Meteorology and Atmospheric Physics, 2024)

Toxicological implications of industrial effluents on plants: a review focusing on phytoremediation techniques - A. Hansa; A. Devi; M. Upadhyay; H. Gupta; K. Syam; B. Asgari Lajayer; R. Sharma (International Journal of Environmental Science and Technology, 2024)

Metal-organic framework-derived LaFeO3@C: An adsorbent for removing organic dyes from water - Veena Lalan; R. Devi Chandra; V.P. Mahadevan Pillai; K.G. Gopchandran (Journal of Environmental Chemical Engineering, 2023)

Mint leaves (Mentha arvensis) mediated CaO nanoparticles in dye degradation and their role in anti-inflammatory, anti-cancer properties - Rajasree Shanmuganathan; Quynh Hoang Le; Sandhanasamy Devanesan; Shaban R M Sayed; V Devi Rajeswari; Xinghui Liu; G.K. Jhanani (Environmental Research, 2023)

Investigation of random noise in SYM-H and Dst during intense geomagnetic storms and solar quiet days of SC 23 using the method of potential analysis - Devi R Nair; P R Prince (Journal of Earth System Science, 2023)

Assessment of Lobster Resources in Coastal Region of Gulf of Mannar, Southeast Coast of India - N. Renuga Devi; A. Ahamed Rasheeq; B. Antrose Preethi; Muthusamy Anand; C. Titus; Sankaralingam Subbiah; Kannan Rangesh; R. Dineshkumar; A. Arumugam (Thalassas: An International Journal of Marine Sciences, 2023)

Effect of algal metabolites in the inhibition of angiogenic channels for breast tumour - Risav Banerjee; Rajdeep Das; Amrutha VM; Asha Devi S; Sudhakaran R (Aquaculture International, 2023)

Microalgae: A green eco-friendly agents for bioremediation of tannery wastewater with simultaneous production of value-added products - Anuradha Devi; Meenakshi Verma; Ganesh Dattatraya Saratale; Rijuta Ganesh Saratale; Luiz Fernando R. Ferreira; Sikandar I. Mulla; Ram Naresh Bharagava (Chemosphere, 2023)

Influence of age, diurnal cycle, and plant and non-plant surfaces on oviposition by Spodoptera litura (Fabricius)(Lepidoptera: Noctuidae) - S. P. Yadav Deen; Anupam Varshney Sharma; Priya Singh; Satish Ganta; P. R. Ragesh; Smriti Sharma; Tarkeshwar; Kapinder; Jyotsna Singh; Mayanglambam Rojina Devi; Sanjiv Mullick (International Journal of Tropical Insect Science, 2023)

Mechanistic Insights into Immune-Microbiota Interactions and Preventive Role of Probiotics Against Autoimmune Diabetes Mellitus - M. Bidyarani Devi; Hridip Kumar Sarma; Ashis K. Mukherjee; Mojibur R. Khan (Probiotics and Antimicrobial Proteins, 2023)

Dunaliella salina fuel blends as the secondary fuel for the microgas turbine engines: A combustion and emission study - R. Gokulnath; P. Booma Devi; Beata Gavurova; Sulaiman Ali Alharbi; Saleh Alfarraj; G.K. Jhanani; Kathirvel Brindhadevi (Fuel, 2023)

Correction: Concurrent Assessment of Oxidative Stress and MT-ATP6 Gene Profiling to Facilitate Diagnosis of Autism Spectrum Disorder (ASD) in Tamil Nadu Population - Balachandar Vellingiri; Dhivya Venkatesan; Mahalaxmi Iyer; Gomathi Mohan; Padmavathi Krishnan; Krothapalli Sai Krishna; Sangeetha R; Arul Narayanasamy; Abilash Valsala Gopalakrishnan; Nachimuthu Senthil Kumar; Mohana Devi Subramaniam (Journal of Molecular Neuroscience, 2023)

Concurrent Assessment of Oxidative Stress and MT-ATP6 Gene Profiling to Facilitate Diagnosis of Autism Spectrum Disorder (ASD) in Tamil Nadu Population - Balachandar Vellingiri; Dhivya Venkatesan; Mahalaxmi Iyer; Gomathi Mohan; Padmavathi Krishnan; Krothapalli Sai Krishna; Sangeetha R; Arul Narayanasamy; Abilash Valsala Gopalakrishnan; Nachimuthu Senthil Kumar; Mohana Devi Subramaniam (Journal of Molecular Neuroscience, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Management of gray mold disease of castor using fungicides - R. Arutselvan; R.D. Prasad; G. Uma Devi; C. Sarada (Indian Phytopathology, 2023)

Are Altered Expression of Vascular Endothelial Growth Factor and Placental Growth Factor Associated with Placental Angiogenesis in Recurrent Pregnancy Loss? - Shehnaz Sultana; M. R. Renjini Devi; Mahesh Kumar Rathod; Penagaluru Pardhanandana Reddy; Venkateshwari Ananthapur (Indian Journal of Clinical Biochemistry, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Assessment of land use and land cover and forest fragmentation in traditional landscape in Manipur, Northeast India - A. R. Devi; T. Shimrah (International Journal of Environmental Science and Technology, 2022)

Endophytic Beauveria bassiana can protect the rice plant from sheath blight of rice caused by Rhizoctonia solani and enhance plant growth parameters - Lipa Deb; Pranab Dutta; R. K. Tombisana Devi; Dwipendra Thakuria; Dipali Majumder (Archives of Microbiology, 2022)

Genomic insights of beta-lactamase producing Klebsiella quasipneumoniae subsp. similipneumoniae belonging to sequence type 1699 from retail market fish, India - Sudha Sajeev; Muneeb Hamza; Gopalan Krishnan Sivaraman; Sandeep Ghatak; Rakshit Ojha; Suresh Kumar Mendem; Devi Murugesan; Claire Raisen; Bibek R. Shome; Mark A. Holmes (Archives of Microbiology, 2022)

Virgin Coconut Oil (VCO) Ameliorates High Fat Diet (HFD)-Induced Obesity, Dyslipidemia and Bestows Cardiovascular Protection in Rats - Shilpa S. Shetty; P. G. Roopashree; S. V. Ramesh; Ajeet Singh; M. Arivalagan; M. R. Manikantan; Ullal Harshini Devi; K. P. Sharmila; K. B. Hebbar; N. Suchetha Kumari (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Feature Extraction and Object Detection Using Fast-Convolutional Neural Network for Remote Sensing Satellite Image - N. Bharatha Devi; A. Celine Kavida; R. Murugan (Journal of the Indian Society of Remote Sensing, 2022)

Upper layer characteristics of the South Eastern Arabian Sea associated with an unusual low saline pool during fag end of southwest monsoon - S Vishnu Narayanan Nampoothiri; Muhammad Shafeeque; V S Arun; B R Smitha; Kusum Komal Karati; K Rasheed; C R Asha Devi; Hashim Manjebrayakath (Journal of Earth System Science, 2022)

Mercury transportation dynamics in the Ganga Alluvial Plain, India: rainwater–groundwater–river water interaction study from hotspot region - V. Devi; M. M. Atique; A. Raju; G. Upreti; D. K. Jigyasu; J. K. Yadav; S. Singh; R. Kar; M. Singh (International Journal of Environmental Science and Technology, 2022)

Seismic velocity imaging of the Kumaon–Garhwal Himalaya, India - Prantik Mandal; D. Srinagesh; R. Vijayaraghavan; G. Suresh; B. Naresh; P. Solomon Raju; Aarti Devi; K. Swathi; Dhiraj K. Singh; D. Srinivas; Satish Saha; M. Shekar; et al. (Natural Hazards, 2022)

Anti-viral activity of methyl 1-chloro-7-methyl-2-propyl-1h-benzo[d] imidazole-5-carboxylate against white spot syndrome virus in freshwater crab (Paratelphusa hydrodromous) - K. Karthikeyan; A. T. Manish Kumar; D. Harshini; G. Pooja; J. Arul Daniel; Pavani Yasam; G. Gracevictoria; M. Priayanka; P. Krishnaraj; R. Vidya; S. Asha Devi; Sabbasani Rajasekhara Reddy; et al. (Aquaculture International, 2022)

Nanotechnology-based approaches applied to nutraceuticals - Akanksha R. Singh; Prasanna Kumar Desu; Ramya Krishna Nakkala; Vanitha Kondi; Sushma Devi; Mohammad Sarwar Alam; Hinna Hamid; Rajani B. Athawale; Prashant Kesharwani (Drug Delivery and Translational Research, 2022)

Solanum torvum mediated synthesis and characterization of silver nanoparticles for antibacterial activities - R. Renuka; K. Renuka Devi; M. Sivakami; T. Thilagavathi (Journal of Plant Biochemistry and Biotechnology, 2021)

Pichia kudriavzevii—a potential soil yeast candidate for improving soil physical, chemical and biological properties - P. Ramya; V. Gomathi; R. Parimala Devi; D. Balachandar (Archives of Microbiology, 2021)

Red fluorescent ultra-small gold nanoclusters functionalized with signal molecules to probe specificity in quorum sensing receptors in gram-negative bacteria - Anurag M. Chahande; Disha Lathigara; Asmita A. Prabhune; R. Nandini Devi (Archives of Microbiology, 2021)

Antifungal activity and molecular docking of phenol, 2,4-bis(1,1-dimethylethyl) produced by plant growth-promoting actinobacterium Kutzneria sp. strain TSII from mangrove sediments - Thangarasu Suganya Devi; Karuppiah Vijay; R. M. Vidhyavathi; Ponnuchamy Kumar; Muthusamy Govarthanan; Thangavel Kavitha (Archives of Microbiology, 2021)

Characterization of earthquake hazard at the Palghar and Pulichintala swarm activity regions (India) through three-dimensional modelling of b-value and fractal (correlation) dimensions - Prantik Mandal; D. Srinagesh; G. Suresh; B. Naresh; Mahalaxmi Naidu; Dhiraj Kumar Singh; K. Swathi; Arti Devi; S. Vittal; P. K. Vengala; R. Vijaya Raghavan; M. Shekar; et al. (Natural Hazards, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Box–Behnken design and experimental study of ciprofloxacin degradation over Ag2O/CeO2/g-C3N4 nanocomposites - D. Pinheiro; K. R. Sunaja Devi; A. Jose; K. Karthik (International Journal of Environmental Science and Technology, 2021)

Morphological and molecular characterization of new plant type core set for yield and culm strength traits in rice (Oryza sativa L.) - Rachana Bagudam; K. B. Eswari; Jyothi Badri; G. Lakshmi Devi; L. R. K. JaiVidhya; P. Bhavani; Gattu Swathi; M. Bharath; P. Raghuveer Rao; Jukanti Aravind Kumar; R. Abdul Fiyaz; C. N. Neeraja; et al. (Journal of Plant Biochemistry and Biotechnology, 2021)

Evaluation of cellulase production from Aspergillus niger and Aspergillus heteromorphus under submerged and solid‐state fermentation - Anita Singh; Somvir Bajar; Arti Devi; Narsi R. Bishnoi (Environmental Sustainability, 2021)

Cryopreservation of shoot tips of Gentiana kurroo Royle – a critically endangered medicinal plant of India - Neelam Sharma; R. Gowthami; S. Vimala Devi; Era Vaidya Malhotra; Ruchira Pandey; Anuradha Agrawal (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Newborn screening and single nucleotide variation profiling of TSHR, TPO, TG and DUOX2 candidate genes for congenital hypothyroidism - Yedukondalu Kollati; Radha Rama Devi Akella; Shaik Mohammad Naushad; Divya Borkar; Maunika Thalla; Swapna Nagalingam; Lokesh Lingappa; Rajesh K. Patel; G. Bhanuprakash Reddy; Vijaya R. Dirisala (Molecular Biology Reports, 2020)

Designing Biomass Rice Husk Silica as an Efficient Catalyst for the Synthesis of Biofuel Additive n-Butyl Levulinate - A. Selva Priya; K. R. Sunaja Devi (BioEnergy Research, 2020)

Anti-inflammatory and anticancer activities of erythrodiol-3-acetate and 2,4-di-tert-butylphenol isolated from Humboldtia unijuga - Reshma V. R. Nair; Devi Velayudhan Jayasree; Prabath Gopalakrishnan Biju; Sabulal Baby (Natural Product Research, 2020)

Dissipation Kinetics of Hexaconazole and Lambda-Cyhalothrin Residue in Soil and Potato Plant - Raginee Devi; R. P. Singh; A. K. Sachan (Potato Research, 2019)

Pansharpening using data-centric optimization approach - Mutum Bidyarani Devi; R Devanathan (International Journal of Remote Sensing, 2019)

Gene Expression Profiling in Sugarcane Genotypes During Drought Stress and Rehydration - K. Devi; P. T. Prathima; R. Gomathi; R. Manimekalai; K. Lakshmi; A. Selvi (Sugar Tech, 2019)

Microzonation, ecological risk and attributes of metals in highway road dust traversing through the Kaziranga National Park, Northeast India: implication for confining metal pollution in the national forest - Upasona Devi; Kaling Taki; Tanya Shukla; Kali P. Sarma; Raza R. Hoque; Manish Kumar (Environmental Geochemistry and Health, 2019)

Genetic Status and Endosymbionts Diversity of Bemisia tabaci (Gennadius) on Hosts Belonging to Family Malvaceae in India - T R Hashmi; S R Devi; A Ahmad; N M Meshram; R Prasad (Neotropical Entomology, 2019)

Frequent introgression of European cauliflowers in the present day cultivated Indian cauliflowers and role of Indian genotypes in the evolution of tropical cauliflower - S. S. Dey; R. Bhatia; Kanika Sharma; Ila Bhardwaj; Chithra Devi Pandey; Chander Parkash; Raj Kumar (Euphytica, 2019)

First report of Lasiodiplodia theobromae associated with stem-end rot of mango in Manipur, India - Rahee Bui; Bireswar Sinha; Ph. Sobita Devi; K. Dinesh; R. K. Dilip (Indian Phytopathology, 2018)

Role of enhanced synoptic activity and its interaction with intra-seasonal oscillations on the lower extended range prediction skill during 2015 monsoon season - S. Abhilash; R. Mandal; A. Dey; R. Phani; S. Joseph; R. Chattopadhyay; S. De; N. K. Agarwal; A. K. Sahai; S. Sunitha Devi; M. Rajeevan (Climate Dynamics, 2018)

Genome-Wide Analysis in Wild and Cultivated Oryza Species Reveals Abundance of NBS Genes in Progenitors of Cultivated Rice - Hukam C. Rawal; S. V. Amitha Mithra; Kirti Arora; Vishesh Kumar; Neha Goel; Dwijesh Chandra Mishra; K. K. Chaturvedi; Anil Rai; S. Vimala Devi; T. R. Sharma; Amolkumar U. Solanke (Plant Molecular Biology Reporter, 2018)

Influence of Diameter Class and Field Conditions on Nutrient Cycling under Toona ciliata M. Roem Trees in North-Western Himalaya - D. R. Bhardwaj; Yogeshwari Devi; Nazir A. Pala; Uday Sharma; Rajesh Kaushal (Environmental Processes, 2018)

Design and synthesis of novel triazole linked pyrrole derivatives as potent Mycobacterium tuberculosis inhibitors - M. Lakshmi Devi; P. Lakshmi Reddy; P. Yogeeswari; D. Sriram; T. Veera Reddy; B. V. Subba Reddy; R. Narender (Medicinal Chemistry Research, 2017)

Treeline advances and associated shifts in the ground vegetation alter fine root dynamics and mycelia production in the South and Polar Urals - Emily F. Solly; Ika Djukic; Pavel A. Moiseev; Nelly I. Andreyashkina; Nadezhda M. Devi; Hans Göransson; Valeriy S. Mazepa; Stepan G. Shiyatov; Marina R. Trubina; Fritz H. Schweingruber; Martin Wilmking; Frank Hagedorn (Oecologia, 2017)

Copper transporters and chaperones: Their function on angiogenesis and cellular signalling - S R Bharathi Devi; Aloysius Dhivya M; K N Sulochana (Journal of Biosciences, 2016)

Identification of Potential Habitat Patches for Connectivity Using Weighted Linear Combination (WLC) and Integral Index of Connectivity (IIC) at East Godavari District, Andhra Pradesh, India - Shanthala Devi B. S; M. S. R Murthy; Debnath Bijan; C. S. Jha (Journal of the Indian Society of Remote Sensing, 2016)

Assessment and comparison of the properties of biodiesel synthesized from three different types of wet microalgal biomass - Katkam N. Gangadhar; Hugo Pereira; Hermínio P. Diogo; Rui M. Borges dos Santos; B. L. A. Prabhavathi Devi; R. B. N. Prasad; Luísa Custódio; F. Xavier Malcata; João Varela; Luísa Barreira (Journal of Applied Phycology, 2016)

Identification and validation of novel alleles of rice blast resistant gene Pi54, and analysis of their nucleotide diversity in landraces and wild Oryza species - G. Ramkumar; M. S. Madhav; S. J. S. Rama Devi; B. Umakanth; M. K. Pandey; M. S. Prasad; R. M. Sundaram; B. C. Viraktamath; V. Ravindra Babu (Euphytica, 2016)

Field level evaluation of rice introgression lines for heat tolerance and validation of markers linked to spikelet fertility - V. Vishnu Prasanth; Kumari Ramana Basava; M. Suchandranath Babu; Venkata Tripura V.G.N.; S. J. S. Rama Devi; S. K. Mangrauthia; S. R. Voleti; N. Sarla (Physiology and Molecular Biology of Plants, 2016)

Design and development of oxobenzimidazoles as novel androgen receptor antagonists - R. Elancheran; K. Saravanan; Bhaswati Choudhury; S. Divakar; S. Kabilan; M. Ramanathan; Babulal Das; R. Devi; Jibon Kotoky (Medicinal Chemistry Research, 2016)

Expression and inheritance of chimeric cry2AX1 gene in transgenic cotton plants generated through somatic embryogenesis - A. R. Sakthi; A. Naveenkumar; P. S. Deepikha; N. Balakrishnan; K. K. Kumar; E. Kokila Devi; V. Balasubramani; L. Arul; P. K. Singh; D. Sudhakar; V. Udayasuriyan; P. Balasubramanian (In Vitro Cellular & Developmental Biology - Plant, 2015)

Response of micro- and mesozooplankton in the southwestern Bay of Bengal to a cyclonic eddy during the winter monsoon, 2005 - K. J. Jayalakshmi; P. Sabu; C. R. Asha Devi; V. N. Sanjeevan (Environmental Monitoring and Assessment, 2015)

Characteristics of a cyclonic eddy and its influence on mesozooplankton community in the northern Bay of Bengal during early winter monsoon - P. Sabu; C. R. Asha Devi; C. T. Lathika; V. N. Sanjeevan; G. V. M. Gupta (Environmental Monitoring and Assessment, 2015)

Biomonitoring of heavy metals in feathers of eleven common bird species in urban and rural environments of Tiruchirappalli, India - Menon Manjula; R. Mohanraj; M. Prashanthi Devi (Environmental Monitoring and Assessment, 2015)

New insights of superoxide dismutase inhibition of pyrogallol autoxidation - T. Ramasarma; Aparna V. S. Rao; M. Maya Devi; R. V. Omkumar; K. S. Bhagyashree; S. V. Bhat (Molecular and Cellular Biochemistry, 2015)

Dual inhibition of arachidonic acid pathway by mulberry leaf extract - Seema Chauhan; Uma Devi; Venkatesh R. Kumar; Vikas Kumar; Firoz Anwar; Gaurav Kaithwas (Inflammopharmacology, 2015)

Prevalence of peste des petits ruminants in goats in North-East India - V. Balamurugan; Sutopa Das; D. S. N. Raju; Indirani Chakravarty; M. Nagalingam; D. Hemadri; G. Govindaraj; N. Ibotombi Singh; Keduzol Ltu; Maitryee Devi; K. Sharma; M. R. Gajendragad; et al. (VirusDisease, 2014)

Studies on Biosynthesis of Antimicrobial Silver Nanoparticles Using Endophytic Fungi Isolated from the Ethno-medicinal Plant Gloriosa superba L. - Lamabam Sophiya Devi; Donald A. Bareh; S. R. Joshi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Persistence and risk assessment of spiromesifen on tomato in India: a multilocational study - K. K. Sharma; Irani Mukherjee; Balwinder Singh; Kousik Mandal; Sanjay K. Sahoo; Hemanta Banerjee; Tirthankar Banerjee; Sankhajit Roy; Paresh G. Shah; Hemlatta K. Patel; Anil R. Patel; S. Naseema Beevi; et al. (Environmental Monitoring and Assessment, 2014)

Activity enhancement of carbonic anhydrase in Chlamydomonas sp. for effective CO2 sequestration - Raju R. Yadav; Kannan Krishnamurthi; Ajam Y. Shekh; Sandeep N. Mudliar; Saravana S. Devi; Tapan Chakrabarti (Clean Technologies and Environmental Policy, 2014)

Residual behavior and risk assessment of flubendiamide on tomato at different agro-climatic conditions in India - K. K. Sharma; Irani Mukherjee; Balwinder Singh; Sanjay K. Sahoo; N. S. Parihar; B. N. Sharma; V. D. Kale; R. V. Nakat; A. R. Walunj; Saudamini Mohapatra; A. K. Ahuja; Debi Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Beyond canonical inflammasomes: emerging pathways in IL-1-mediated autoinflammatory disease - John R. Lukens; Thirumala-Devi Kanneganti (Seminars in Immunopathology, 2014)

Post tsunami mangrove evaluation in coastal vicinity of Andaman Islands, India - Apurba Kumar Das; Dilip Kumar Jha; M. Prashanthi Devi; Biraja Kumar Sahu; N. V. Vinithkumar; R. Kirubagaran (Journal of Coastal Conservation, 2014)

A comparative study on mesozooplankton abundance and diversity between a protected and an unprotected coastal area of Andaman Islands - Honey U. K. Pillai; K. V. Jayalakshmy; A. Biju; K. J. Jayalakshmi; V. T. Paulinose; C. B. L. Devi; V. R. Nair; C. Revichandran; N. R. Menon; C. T. Achuthankutty; S. U. Panampunnayil (Environmental Monitoring and Assessment, 2014)

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Assessment of 222Rn emanation from ore body and backfill tailings in low-grade underground uranium mine - Devi Prasad Mishra; Patitapaban Sahu; Durga Charan Panigrahi; Vivekanand Jha; R. Lokeswara Patnaik (Environmental Science and Pollution Research, 2014)

Assessment of coastal dune characteristics using georadar imaging and sedimentological analysis: Odisha and Visakhapatnam, India - K. Devi; M. C. Raicy; Deshraj Trivedi; P. Srinivasan; S. G. N. Murthy; Ronald J. Goble; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Synthesis, Structural, Thermal and Photo-Physical Properties of Triazine Based NLO Material - M. Shyamala Devi; P. Tharmaraj; C. D. Sheela; R. Ebenezer (Journal of Fluorescence, 2013)

Fungal biodegradation of phthalate plasticizer in situ - S. Pradeep; P. Faseela; M. K. Sarath Josh; S. Balachandran; R. Sudha Devi; Sailas Benjamin (Biodegradation, 2013)

Comparison of common bean (Phaseolus vulgaris L.) genotypes for nitrogen fixation tolerance to soil drying - Mura Jyostna Devi; Thomas R. Sinclair; Stephen E. Beebe; Idupulapati M. Rao (Plant and Soil, 2013)

Integrated approach of assessing sedimentary characteristics of onshore sand deposits on the Velankanni coast, Tamil Nadu, India: sheds light on extreme wave event signatures - K. Devi; C. S. Vijaya Lakshmi; M. C. Raicy; P. Srinivasan; S. G. N. Murthy; S. M. Hussain; Ilya Buynevich; Rajesh R. Nair (Journal of Coastal Conservation, 2013)

Application of a Chimeric Protein Construct having Enterotoxin B and Toxic Shock Syndrome Toxin Domains of S. aureus in Immunodiagnostics - R. Shylaja; Devi Kalyan Kumar Thakasi; H. S. Murali; K. Prakash Narayana Reddy; H. V. Batra (Indian Journal of Microbiology, 2012)

Recent Advancements in Carbonic Anhydrase–Driven Processes for CO 2 Sequestration: Minireview - Ajam Yakub Shekh; Kannan Krishnamurthi; Sandeep N. Mudliar; Raju R. Yadav; Abhay B. Fulke; Sivanesan Saravana Devi; Tapan Chakrabarti (Critical Reviews in Environmental Science and Technology, 2012)

Enhanced abundance of tintinnids under elevated CO2 level from coastal Bay of Bengal - Haimanti Biswas; Subhadra Devi Gadi; V. Venkata Ramana; M. Durga Bharathi; R. Kesava Priyan; D. Taruni Manjari; M. Dileep Kumar (Biodiversity and Conservation, 2012)

Lower Oligocene bivalves of Ramanian Stage from Kachchh, Gujarat, India - R P Kachhara; R L Jodhawat; K Bigyapati Devi (Journal of Earth System Science, 2012)

Alkaline lipase activity from the marine protists, thraustochytrids - R. Kanchana; Usha Devi Muraleedharan; Seshagiri Raghukumar (World Journal of Microbiology and Biotechnology, 2011)

Monitoring the Disulfide Bond Formation of a Cysteine-Rich Repeat Protein from Helicobacter pylori in the Periplasm of Escherichia coli - Venkataramani Sathya Devi; Peer R. E. Mittl (Current Microbiology, 2011)

Application of GIS for Evaluation and Design of Watershed Guidelines - R. S. Bhalla; Neil W. Pelkey; K. V. Devi Prasad (Water Resources Management, 2011)

Relative efficacy of strobilurin formulations in the control of downy mildew of sunflower - J. Sudisha; S. R. Niranjana; S. L. Sukanya; R. Girijamba; N. Lakshmi Devi; H. Shekar Shetty (Journal of Pest Science, 2010)

Geospatial modelling for identification of potential ecological corridors in Orissa - A. Roy; B. S. S. Devi; B. Debnath; M. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2010)

Oxidative stress in erythrocytes: a study on the effect of antioxidant mixtures during intermittent exposures to high altitude - R. Vani; C. S. Shiva Shankar Reddy; S. Asha Devi (International Journal of Biometeorology, 2010)

Sarcoptic mange infestation in pigs in a hilly region of Meghalaya - M. Das; R. Laha; P. Devi; R. K. Bordoloi; S. Naskar (Tropical Animal Health and Production, 2010)

Genotypic variability among peanut (Arachis hypogea L.) in sensitivity of nitrogen fixation to soil drying - M. Jyostna Devi; Thomas R. Sinclair; Vincent Vadez (Plant and Soil, 2010)

Polymorphisms in the vitamin D receptor and the androgen receptor gene associated with the risk of urolithiasis - Rama Devi Mittal; D. K. Mishra; P. Srivastava; P. Manchanda; H. K. Bid; R. Kapoor (Indian Journal of Clinical Biochemistry, 2010)

Effect of Cyclodextrin Complexation of Curcumin on its Solubility and Antiangiogenic and Anti-inflammatory Activity in Rat Colitis Model - Vivek R. Yadav; Sarasija Suresh; Kshama Devi; Seema Yadav (AAPS PharmSciTech, 2009)

Genotoxicity of sludges, wastewater and effluents from three different industries - K. Krishnamurthi; S. Saravana Devi; J. G. Hengstler; Matthias Hermes; Koel Kumar; Dipanwita Dutta; S. Muhil Vannan; T. S. Subin; R. R. Yadav; T. Chakrabarti (Archives of Toxicology, 2008)

Treatment with bindarit, an inhibitor of MCP-1 synthesis, protects mice against trinitrobenzene sulfonic acid-induced colitis - M. Bhatia; C. Landolfi; F. Basta; G. Bovi; R. Devi Ramnath; A. Capezzone de Joannon; A. Guglielmotti (Inflammation Research, 2008)

Molecular characterization of reciprocal crosses of Aerides vandarum and Vanda stangeana (Orchidaceae) at the protocorm stage - Rajkumar Kishor; H. S. Devi; K. Jeyaram; M. R. K. Singh (Plant Biotechnology Reports, 2008)

Stress-inducible expression of At DREB1A in transgenic peanut (Arachis hypogaea L.) increases transpiration efficiency under water-limiting conditions - Pooja Bhatnagar-Mathur; M. Jyostna Devi; D. Srinivas Reddy; M. Lavanya; Vincent Vadez; R. Serraj; K. Yamaguchi-Shinozaki; Kiran K. Sharma (Plant Cell Reports, 2007)

Cannabinoid CB2 Receptor-Mediated Anti-nociception in Models of Acute and Chronic Pain - Maulik D. Jhaveri; Devi R. Sagar; Steven J. R. Elmes; David A. Kendall; Victoria Chapman (Molecular Neurobiology, 2007)

Isolation and characterisation of bioactive isoflavonoids from the roots of Dalbergia horrida - Manoj C. Narayanan; Priya R. Rao; Nagarajan N. Shanmugam; Sethuraman M. Gopalakrishnan; Kshama Devi (Natural Product Research, 2007)

Identification of a high frequency of chromosomal rearrangements in the centromeric regions of prostate cancer patients - V. Balachandar; B. Lakshman Kumar; K. Sasikala; P. Manikantan; R. Sangeetha; S. Mohana Devi (Journal of Zhejiang University-SCIENCE B, 2007)

Chemical Oxygen Demand (COD) Reduction in Domestic Wastewater by Fly Ash and Brick Kiln Ash - Rani Devi; R. P. Dahiya (Water, Air, & Soil Pollution, 2006)

Biodiversity Conservation in Sacred Groves of Manipur, Northeast India: Population Structure and Regeneration Status of Woody Species - Ashalata Devi Khumbongmayum; M. L. Khan; R. S. Tripathi (Biodiversity and Conservation, 2006)

Zinc and Calcium Reduce Lead Induced Perturbations in the Aminergic System of Developing Brain - R. P. Jaya Prasanthi; G. Hariprasad Reddy; C. Bhuvaneswari Devi; G. Rajarami Reddy (BioMetals, 2005)

Detection and quantification of poly-ADP-ribosylated cellular proteins of spleen and liver tissues of mice in vivo by slot and Western blot immunoprobing using polyclonal antibody against mouse ADP-ribose polymer - R. N. Sharan; B. Jaylata Devi; J. O. Humtsoe; Jyoti R. Saikia; L. Kma (Molecular and Cellular Biochemistry, 2005)

Sacred groves of Manipur, northeast India:biodiversity value, status and strategies for their conservation - Ashalata Devi Khumbongmayum; M. L. Khan; R. S. Tripathi (Biodiversity and Conservation, 2005)

Altered structure and expression of RB1 gene and increased phosphorylation of pRb in human vestibular schwannomas - R. Thomas; P. D. Antony Herold Prabhu; J. Mathivanan; Rohini; D. Sivakumar; P. N. Jayakumar; B. Indira Devi; S. Satish; K. V. R. Sastry; R. Gope (Molecular and Cellular Biochemistry, 2005)

The TATGARAT Box of the HSV-1 ICP27 Gene is Essential for Immediate Early Expression but not Critical for Efficient Replication in vitro or in vivo - Aixu Sun; G. Devi-Rao; M. Rice; L. Gary; D. Bloom; R. Sandri-Goldin; P. Wagner (Virus Genes, 2004)

Spectroscopic and Photophysical Characterization of Fluorescent Chemosensors for Monosaccharides Based on N-Phenylboronic Acid Derivatives of 1,8-Naphthalimide - Nicolas DiCesare; Devi P. Adhikari; Justin J. Heynekamp; Michael D. Heagy; Joseph R. Lakowicz (Journal of Fluorescence, 2002)

Plant regeneration from scutella of immature embryos of diverse sorghum genotypes - R. V. Sairam; N. Seetharama; T. Shyamala; P. S. Devi (Cereal Research Communications, 2000)

Culture and regeneration of mesophyll-derived protoplasts of sorghum [ Sorghum bicolor (L.) Moench] - R. V. Sairam; N. Seetharama; P. S. Devi; A. Verma; U. R. Murthy; I. Potrykus (Plant Cell Reports, 1999)

Microprojectile-mediated transient and integrative transformation of rice embryogenic suspension cells: effects of osmotic cell conditioning and of the physical configuration of plasmid DNA - Y. L. Nandadeva; C. G. Lupi; C. S. Meyer; P. S. Devi; I. Potrykus; R. Bilang (Plant Cell Reports, 1999)

Nitrous oxide emissions under different soil and land management conditions - C. Henault; X. Devis; S. Page; E. Justes; R. Reau; J. C. Germon (Biology and Fertility of Soils, 1998)

Immunomodulation of excretory secretory materials from the filarial parasiteSetaria digitata - R. Kaleysa Raj; C. G. Pradeep; C. Maya Devi; Linda John; M. R. Rekha; Sheeba K. Oommen (Indian Journal of Clinical Biochemistry, 1997)

Glycoprotein components in the serum of patients with cancer breast - Miriam Varkey; R. Sundara Devi; Shrinivas B. Rao (Indian Journal of Clinical Biochemistry, 1997)